A COMPARATIVE STUDY BETWEEN CHARACTERISTICS SEEN IN SUPERVISED VERSUS NON SUPERVISED EMPLOYEES - Silveira, Cedric Thomas (International Journal of Research -GRANTHAALAYAH, 2021)
Supervised and unsupervised employees are assumed to be quite different. A supervised employee can always fall back to the supervisor in times of need as compared to an unsupervised employee who has to fend for himself in most times. Wishing to find out as to what keeps supervised as well as unsupervised employees going in an organization, I drew up a questionnaire to be filled up by the employees. The questionnaire had six variables which had to be ranked from 1 to 6, with 1 being the most important and 6 being the least important. The variables were Discipline, Growth, Desire to learn, Organizational skills, Dedication, and Motivation. A total of 100 employees were interviewed, 50 who were supervised and 50 who were not supervised. A personal interview was conducted wherein the questionnaire was direct and structured. The results were such among the supervised employees growth was ranked first followed by discipline and desire to learn whereas among the unsupervised employees growth was ranked first followed by desire to learn and motivation.